PENGETAHUAN PETANI DALAM BUDIDAYA CABAI RAWIT DI DESA LAPANDEWA MAKMUR KECAMATAN LAPANDEWA KABUPATEN BUTON SELATAN - Safran, Safran; Abdullah, Sukmawati; Jayadisastra, Yoenita; Dima, Darsilan (Universitas Halu Oleo, 2024)
Cayenne pepper cultivation represents one of the most promising agricultural enterprises in the region, offering significant potential for growth and development. The objective of this study was to assess the level of knowledge and expertise among farmers engaged in the cultivation of cayenne pepper plants in Lapandewa Makmur Village, Lapandewa District, South Buton Regency. The population of interest in this study was the total number of cayenne pepper farmers in Lapandewa Makmur Village, which was 22 farmers. The sample was determined using the census method, whereby the total population was used as a sample in the study, namely 22 respondents. Data collection techniques employed observation, interview, and documentation methods using media in the form of questionnaires. This research is quantitative in nature. Data were processed using quantitative descriptive analysis using the class interval formula. The results indicated that the level of knowledge of farmers in cayenne pepper cultivation activities in Lapandewa Makmur Village was at a high level of knowledge category. This level of knowledge encompasses the following areas: seed procurement, land processing, planting, maintenance, pest control, harvest, and post-harvest. The farmers demonstrated an adequate level of knowledge regarding the processes of seed procurement, land processing, planting, pest control, harvesting, and post-harvesting. However, they exhibited an insufficient level of knowledge regarding the maintenance of cayenne pepper plants.